ECONOMIC STRUCTURE AND ECONOMIC SHIFT ANALYSIS OF FOOD CROP COMMODITIES IN SOUTH LAMPUNG REGENCY - Rizky Augia; Teguh Endaryanto; Novi Rosanti (Universitas Sebelas Maret, 2025)
Research on the economic structure and shifts of the food crop commodities in South Lampung Regency is important to identify local potential that can be optimized to support regional food sovereignty. This study specifically aims to determine the leading commodities within the food crop subsector that should be prioritized for regional development. The research uses secondary data obtained from the Central Bureau of Statistics (BPS) and the Department of Food Crops, Horticulture, and Plantations of South Lampung Regency, focusing on soybean, sweet potato, maize, mung bean, rice, peanut, and cassava as the main food crops distributed across 17 districts, forming 119 commodity–district observation units. The methods used to identify the structure of food crop commodities in the economy of South Lampung Regency include the location quotient, dynamic location quotient, localization index, and specialization index, while the shift-share analysis was applied to examine the economic shifts of food crop commodities. Additionally, Klassen typology was used to classify commodity–district combinations into four quadrants. The results of the economic structure analysis show that 25 observation units fall into the base and prospective categories, with rice in Candipuro District and cassava in Jati Agung District also showing distinct concentration and characteristics. Based on the results of the economic shift analysis, rice in Candipuro District ranks highest in terms of growth and competitiveness, thus being designated as the region’s leading commodity that can serve as a foundation for sustainable agricultural development planning and the strengthening of national food sovereignty.